1999
DOI: 10.1161/01.hyp.33.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) Reduces Smooth Muscle Growth After Vascular Injury

Abstract: Abstract-Regulation of vascular smooth muscle cell growth is critical to the maintenance of normal blood flow and vessel patency. Angiotensin-(1-7) [Ang-(1-7)] inhibits proliferation of vascular smooth muscle cells in vitro and opposes the mitogenic effects of angiotensin II. The present study investigated whether Ang-(1-7) inhibits vascular smooth muscle cell growth in vivo by determining its effect on neointimal formation and medial remodeling in balloon-injured carotid arteries. The carotid arteries of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(141 citation statements)
references
References 35 publications
6
127
1
7
Order By: Relevance
“…In a follow-up study from our group, Ang-(1-7) administered continuously for 12 days after carotid artery balloon catheter injury inhibited neointimal formation compared to saline-infused control rats (Strawn et al 1999). Elevated endogenous Ang-(1-7) by ACE inhibition or angiotensin receptor blockade also yielded similar results.…”
Section: Ang-(1-7) and Growthmentioning
confidence: 68%
See 1 more Smart Citation
“…In a follow-up study from our group, Ang-(1-7) administered continuously for 12 days after carotid artery balloon catheter injury inhibited neointimal formation compared to saline-infused control rats (Strawn et al 1999). Elevated endogenous Ang-(1-7) by ACE inhibition or angiotensin receptor blockade also yielded similar results.…”
Section: Ang-(1-7) and Growthmentioning
confidence: 68%
“…It is well documented that Ang II promotes cell proliferation (Daemen et al 1991;Su et al 1998) and vasoconstriction (Wackenfors et al 2004), whereas Ang-(1-7) has antiproliferative actions on cardiac myocytes (Tallant et al 2005) and vascular smooth muscle (Strawn et al 1999), and is a vasodilator . These actions have uncovered a new way to think about the RAS, both conceptually and therapeutically.…”
Section: Angiotensin-(1-7) 163mentioning
confidence: 99%
“…7 In addition to its vascular effects, it was shown that Ang-(1-7) also has beneficial effects on cardiac function. [9][10][11] Moreover, it opposes the growth-stimulating effects of Ang II in vascular smooth muscle cells 12 and cardiomyocytes. 13 Ang-(1-7) also demonstrates effects on renal function by participating in the control of water and electrolyte homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that angiotensin [1][2][3][4][5][6][7] possesses the ability to stimulate the release of vasodilator prostanoids and nitric oxide, as well as inhibiting proliferation of vascular smooth muscle cells in balloon injured carotid arteries and rat aorta. [29][30][31] Angiotensin II may also be generated via the action of tonin. Tonin, a kallikrenin-like protease has the ability to form angiotensin II from angiotensin I as well as directly from the synthetic renin substrate and from human angiotensinogen.…”
Section: Alternative Angiotensin II Generating Enzymesmentioning
confidence: 99%